The Role of E-wom in TikTok Shop in Improving Purchase Decisions with Brand Awareness and Viral Trends as Intervening Variables - Adellia Amandasari; Agus Dwi Cahya; Bernadetta Diansepti Maharani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of Electronic Word of Mouth (e-WOM) on Purchase Decision among TikTok Shop users, with Brand Awareness and Viral Trends as intervening variables. A quantitative approach was used with the SEM-PLS method on 120 active TikTok users who had made purchases through TikTok Shop. The results show that e-WOM has a positive and significant effect on purchase decisions, as well as a significant effect on Brand Awareness and Viral Trends. However, Brand Awareness was not found to have a direct effect on purchase decisions and did not mediate the relationship between e-WOM and purchase decisions. Conversely, Viral Trends acted as a significant mediating variable in strengthening the effect of e-WOM on purchase decisions. These findings indicate that in the context of TikTok Shop, viral phenomena and product popularity play a more dominant role in driving purchase decisions than mere brand awareness.